2008
DOI: 10.1111/j.1365-2893.2008.00980.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon and ribavirin therapy does not select for resistance mutations in hepatitis C virus polymerase

Abstract: Ribavirin has a minor and transient effect on hepatitis C virus (HCV) replication and has been suggested to select a novel mutation, F415Y, in the RNA-dependent RNA polymerase of subtype 1a viruses. Twenty-nine patients with chronic hepatitis C (subtyped by INNO LiPA as 1a, 17; 1b, 11; 1a/1b, 1) who were nonresponders to interferon-based therapies were identified retrospectively and screened at Baseline, week 24 of treatment, and 24 weeks post-treatment. Selection of resistance mutations, including at amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Variances in estimating quasispecies complexity can be influenced by technical limitations and methodological bias [23,24]. Perhaps the emerging methodology of pyrosequencing will assist in establishing the spectrum of quasispecies mutants more precisely at a time before the initiation of antiviral therapy [25,26]. Does virus present in the periphery represent an optimal sample to determine the existence of non-wild-type virions, and does the phenomenon of archiving of quasispecies play a significant role in the reemergene of variants in HCV infections, as it does for HIV and HBV [2,14]?…”
Section: (See the Article By Bartels Et Al On Pages 800 -7)mentioning
confidence: 99%
“…Variances in estimating quasispecies complexity can be influenced by technical limitations and methodological bias [23,24]. Perhaps the emerging methodology of pyrosequencing will assist in establishing the spectrum of quasispecies mutants more precisely at a time before the initiation of antiviral therapy [25,26]. Does virus present in the periphery represent an optimal sample to determine the existence of non-wild-type virions, and does the phenomenon of archiving of quasispecies play a significant role in the reemergene of variants in HCV infections, as it does for HIV and HBV [2,14]?…”
Section: (See the Article By Bartels Et Al On Pages 800 -7)mentioning
confidence: 99%
“…In contrast, other results showed only transient (30) or no (31) increases in substitution rates in NS5B and NS3/4A, respectively. Selection for a ribavirin-associated resistance mutation in NS5B that is suggestive of a mutagenic effect of ribavirin (26) was not verified in nonresponder patients who were treated with ribavirin in combination with IFN-␣ or PEG-IFN-␣ (32). In this study, we employed ultradeep sequencing of the HCV coding region (nucleotides [nt] 330 to 9351) in order to investigate the ribavirin-induced mutagenesis of the viral quasispecies in detail over time in 12 patients under ribavirin monotherapy versus placebo.…”
mentioning
confidence: 99%
“…However, subsequent studies done in Japan and the UK could not find an evident relationship between specific selection of NS5B 415 mutations and the treatment of combination therapy of peginterferon and ribavirin. Sugihara et al reported that they did not find specific mutations in NS5B 415 in the both serum obtained before and after therapy in 18 patients infected with genotype-1b HCV [79], and Ward et al could not find evidence of a relationship of these mutations in the therapy of peginterferon and ribavirin in 15 patients infected with genotype-1a [80]. Hamano et al explored genetic changes of genotype-1b HCV during the treatment of interferonalpha and ribavirin, and reported that mutations at positions 300-358 of NS5B, including polymerase motif B-E, occurred more frequently in SVR patients or in end-oftreatment response patients when compared to nullresponse patients [81].…”
Section: Ns5bmentioning
confidence: 98%